Small business entrepreneurs in vertical marketing systems - Winarto, Vincentius (Cranfield University, 1986)
The objective of this study is to investigate the potential contribution of vertical marketing systems to the development of small business entrepreneurs and in particular to entrepreneurially disadvantaged groups. The following are the two major questions for this study: 1. Do vertical linkage systems serve as a pathway for the entrepreneurially disadvantaged groups, namely those with no entrepreneurial experience, from families without business background, and from indigenous ethnic groups? The modernization process in Third World countries, and in particular Indonesia, may create a widening gap between the modern and the traditional sectors. Vertical relationship systems with their unique characteristics (e. g. a symbiotic relationship between large and small business operation) may contribute towards reducing this gap through developing the entrepreneurially disadvantaged groups into business careers. 2. Do vertical relationships accomodatb, independent entrepreneurs? It is assumed that independent entrepreneurs can perform better entrepreneurial functions than those "entrepreneurs" who are constrained by external power. There are doubts whether the vertical relationship, characterized by a large firm's dominant role, can accomodate independent entrepreneurs. This study reveals that despite many problems and limitations a tight-control type of vertical marketing system can serve as a pathway for individuals from entrepreneurially disadvantaged groups to become successful modern-type entrepreneurs. The performance of these disadvantaged groups is equal to that of other different groups. Also, independent entrepreneurs exist in all the vertical marketing systems studied.